The p53 Tumor Suppressor in the Control of Metabolism and Ferroptosis - Gnanapradeepan, Keerthana; Basu, Subhasree; Barnoud, Thibaut; Budina-Kolomets, Anna; Kung, Che-Pei; Murphy, Maureen E. (Frontiers in Endocrinology, 2018)
The p53 tumor suppressor continues to be distinguished as the most frequently mutated gene in human cancer. It is widely believed that the ability of p53 to induce senescence and programmed cell death underlies the tumor suppressor functions of p53. However, p53 has a number of other functions that recent data strongly implicate in tumor suppression, particularly with regard to the control of metabolism and ferroptosis (iron- and lipid-peroxide-mediated cell death) by p53. As reviewed here, the roles of p53 in the control of metabolism and ferroptosis are complex. Wild-type (WT) p53 negatively regulates lipid synthesis and glycolysis in normal and tumor cells, and positively regulates oxidative phosphorylation and lipid catabolism. Mutant p53 in tumor cells does the converse, positively regulating lipid synthesis and glycolysis. The role of p53 in ferroptosis is even more complex: in normal tissues, WT p53 appears to positively regulate ferroptosis, and this pathway appears to play a role in the ability of basal, unstressed p53 to suppress tumor initiation and development. In tumors, other regulators of ferroptosis supersede p53’s role, and WT p53 appears to play a limited role; instead, mutant p53 sensitizes tumor cells to ferroptosis. By clearly elucidating the roles of WT and mutant p53 in metabolism and ferroptosis, and establishing these roles in tumor suppression, emerging research promises to yield new therapeutic avenues for cancer and metabolic diseases.